Quantitative Evolution of WC-Co Cemented Carbide Tool Surface during the Cold Forming of Steel Parts - Debras, Colin; Dubar, Mirentxu; Dubar, Laurent; Dubois, André (Key engineering materials, 2018)
The present paper investigates the evolution of the WC grain size and morphology with the number of produced parts. Four reduction dies used in cold forward extrusion of steel are taken from the production line: a brand new die and three dies which have respectively produced 100.000, 150.000 and 220.000 parts. 3D roughness measurements and SEM micrographs are performed on the contact surface of each die. Results of these analyses highlight that WC grains are subject to plastic strain and are removed from the surface as the number of produced parts increase, leading to a growth of WC free areas where steel adhesion may occur. When analyzing the size of the WC grains, it appears that the population of small grains increases with the number of produced parts until 150.000. Then the population of small grains decreases. A wear mechanism is proposed to explain this variation of WC grains size with the number of extruded parts.